(untitled) (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
This “study aims to analyze the effect of operating expenses and business income on net profit at PT. Tunas Antarnusa Muda Bandar Lampung for the period 2018–2024. The research method used is quantitative with secondary data in the form of company income statements. Data analysis techniques include descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis testing using F and t tests. The results show that, partially, operating expenses do not have a significant effect on net profit, and operating income also does not have a significant effect on net profit. However, simultaneously, operating expenses and operating income significantly affect net profit with a coefficient of determination of 83.6%, indicating that these two variables can explain most of the variation in company net profit. This finding indicates that a company’s net profit is not only influenced by one factor individually, but by a combination of operational expense management and business income achievement. Therefore, companies need to improve operational efficiency and optimize income growth strategies in order to achieve more stable and sustainable net profits